Effect of Grinding Media on Grinding-Flotation Behavior of Chalcopyrite and Pyrite - Liao, Ningning; Wu, Caibin; Xu, Jindong; Feng, Bo; Wu, Ji; Gong, Yuan (Frontiers in Materials, 2020)
Grinding media have significant influence on the flotation of chalcopyrite and pyrite. This effect is mainly related to the change in the surface properties of chalcopyrite and pyrite. This paper investigates the influence of steel ball and nano-ceramic ball grinding on the floatability of chalcopyrite and pyrite. Flotation results, as well scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), ultraviolet spectrophotometer, and zeta potential measurement results indicate that nano-ceramic ball grinding is beneficial to the flotation of chalcopyrite. Flotation results also indicate that chalcopyrite has better floatability after nano-ceramic ball grinding compared with steel ball grinding. Results of adsorption experiments show that nano-ceramic media grinding contributes to the adsorption of chalcopyrite and isobutyl xanthate. XPS and SEM techniques demonstrated that steel ball grinding easily produces oxidation species at the surface of chalcopyrite, thereby reducing its floatability. Results from this study also confirmed that steel ball grinding is beneficial to the flotation of pyrite. Therefore, nano-ceramic media grinding produces better selective flotation in chalcopyrite than steel media grinding.